A glass-ceramic baking tray and production method thereof
By preparing a covered glass layer and non-stick coating on the porous structural surface of the microcrystalline glass baking tray, the problem of food oxidation or charring during high-temperature baking is solved, and good hydrophobic and oleophobic properties and high thermal conductivity are achieved, and the service life of the non-stick coating is extended.
Patent Information
- Application Number
- CN202510097800.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing microcrystalline glass baking tray is prone to oxidation or charring when baking at high temperatures, and the non-stick coating is prone to cracking, affecting the cleanliness and health and safety.
The binding force and heat conduction area between the non-stick coating and the microcrystalline glass body is enhanced by preparing a covered microcrystalline glass layer on the surface of the microcrystalline glass body by combining the non-stick coating and the microcrystalline glass body.
It achieves good hydrophobic and oleophobic properties and high thermal conductivity of microcrystalline glass baking trays, extends the service life of the non-stick coating, and improves cleaning and health and safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass, and in particular relates to a glass-ceramic baking tray and a production method thereof. Background Art
[0002] As people's living standards improve, ovens are used more and more frequently in daily life. Baking trays are indispensable items in ovens. Due to the high temperature in the oven, food is easily burnt and sticks to the baking tray, which is difficult to clean. In the prior art, non-stick coatings are usually used to improve the non-stick performance of baking trays. However, due to uneven heating between the baking tray body and the coating, the coating cracks and fails, and the coating also sticks to the food, which is harmful to the human body.
[0003] Patent CN107713776A discloses a method for producing microcrystalline glass baking trays. The produced microcrystalline glass baking trays are lightweight, high temperature resistant, acid and alkali resistant, do not require coating and will not rust, thus better protecting the environment and human health. However, high temperature baking during use can easily cause food to oxidize or even carbonize, causing food to adhere to the glass baking tray and be difficult to clean. This is not only unsightly, but multiple baking can also easily produce carcinogens, affecting physical health.
[0004] Patent CN107973532A discloses a glass baking tray with non-stick function and a method for making the same. The glass baking tray is provided with a non-stick function by coating a primer and a topcoat inside the glass baking tray, so as to facilitate cleaning. However, the main components of the primer and the topcoat in this solution are silica sol, and the thermal conductivity of silica sol is much lower than that of microcrystalline glass. When heated, the paint surface is prone to cracking due to uneven heat transfer, thereby losing the non-stick property.
[0005] Therefore, there is a need for a glass-ceramic baking tray that has good thermal conductivity, is hydrophobic and oleophobic, and is easy to clean. Summary of the invention
[0006] The purpose of the present invention is to improve the hydrophobicity and oleophobicity of a glass-ceramic baking tray while having good thermal conductivity, and to provide a glass-ceramic baking tray and a production method thereof.
[0007] The present invention prepares a covering microcrystalline glass layer with a porous structure on the surface of a microcrystalline glass blank, and utilizes the plating between the porous structure and the non-stick coating to enhance the bonding force and heat conduction area between the non-stick coating and the microcrystalline glass blank, thereby enhancing the thermal conductivity of the microcrystalline glass baking tray. The non-stick coating has strong bonding force and is not easy to crack.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A method for producing a glass-ceramic baking tray comprises the following steps:
[0010] Step 1: Mix granite powder, foaming agent and calcium hydroxide to obtain a mixed powder, granulate the mixed powder with a 5wt% polyvinyl alcohol aqueous solution, press it into a mold, dry it, heat it to 500-550℃ and heat treat it for 2-2.5h to obtain a porous glass body, crush and grind the porous glass body and pass it through a 100-mesh sieve to obtain a porous glass powder.
[0011] Step 2: Disperse the porous glass powder in a 5wt% polyvinyl alcohol solution to obtain a coating material, and evenly coat the coating material on the microcrystalline glass body with a coating thickness of 0.1-0.5mm. Then place it in a mold and heat it to 500-550℃ for heat treatment for 2-2.5h. Transfer it to a muffle furnace and heat it to 1150-1250℃ for reaction for 20-25min. After cooling, polish the surface to obtain a porous microcrystalline glass body.
[0012] Step three: add methyltrimethoxysilane to ethanol in a reaction kettle, add nano-silica with a particle size of 10-20 nm, stir magnetically for 4-5 hours, remove the solvent by rotary evaporation, dry at 80-90°C, add polydimethylsiloxane and n-hexane, and obtain a suspension by ultrasonic dispersion. Spray the suspension evenly on the surface of the porous microcrystalline glass body with a spray gun, and then place it in an oven at 200-250°C to dry for 30-40 minutes. Repeat the spraying and drying until the surface of the porous microcrystalline glass body is smooth to obtain a microcrystalline glass baking tray.
[0013] Furthermore, in step 1, the usage ratio of granite powder, foaming agent and calcium hydroxide is 50-100g: 2.5-5g: 2-2.5g.
[0014] In step 2, the usage ratio of porous glass powder to polyvinyl alcohol solution is 50-100 g: 1-1.5 L.
[0015] In step 3, the dosage ratio of methyltrimethoxysilane, ethanol, nano-silicon dioxide, polydimethylsiloxane and n-hexane is 2-3 mL: 100-150 mL: 0.5-1 g: 80-100 mL: 4-5 mL.
[0016] Further, the foaming agent is prepared by the following steps:
[0017] Disperse silicon dioxide / graphene nanosheets in propanol in a reaction kettle, add ferric nitrate nonahydrate into the reaction kettle and stir to dissolve, then add glycerol, heat to 180-200° C. and react for 16-18 hours, wash and dry after cooling, and calcine in air at 350-370° C. for 2-2.5 hours to obtain a foaming agent.
[0018] Furthermore, the usage ratio of silicon dioxide / graphene nanosheets, propanol, ferric nitrate nonahydrate and glycerol is 5-10 g: 0.8-1 L: 4-6 g: 200-250 mL.
[0019] Further, the silicon dioxide / graphene nanosheets are prepared by the following steps:
[0020] The modified silica nanospheres are dispersed in ethanol in a reaction kettle, the temperature is raised to 60-70° C., nitrogen-doped graphene nanosheets are added, the reaction is stirred for 3-4 hours, and the silica / graphene nanosheets are obtained by drying and precipitating after filtration.
[0021] Furthermore, the usage ratio of the modified silica nanospheres, ethanol and nitrogen-doped graphene nanosheets is 5-10 g: 0.5-1 L: 5-10 g.
[0022] Further, the modified silica nanospheres are prepared by the following steps:
[0023] Ammonia water, deionized water and ethanol were mixed in a reaction kettle, ethyl orthosilicate was dissolved in an equal volume of ethanol to obtain a mixed solution, the mixed solution was slowly added dropwise to the reaction kettle and stirred for 3-4 hours, phenyltriethoxysilane was dissolved in ten times the volume of ethanol, and the solution was slowly added dropwise to the reaction kettle, stirred for reaction for 2-3 hours, the precipitate was washed by centrifugation, and the modified silica nanospheres were obtained after drying.
[0024] Furthermore, the usage ratio of ammonia water, deionized water, ethanol, mixed solution and phenyltriethoxysilane is 20-30mL: 60-80mL: 200-250mL: 40-60mL: 2-4mL.
[0025] Further, nitrogen-doped graphene nanosheets are prepared by the following steps:
[0026] In a reaction kettle, graphene oxide nanosheets with a sheet diameter of 5-10 μm and a thickness of 3-10 nm are dispersed in deionized water and ultrasonically dispersed for 1-1.5 hours. Melamine is added to the reaction kettle, and the temperature is raised to 80-90° C. and stirred for reaction for 12-16 hours. The precipitate is collected by suction filtration and vacuum dried at 60-70° C. The dried powder is heated to 850-900° C. in an argon atmosphere and pyrolyzed for 1-1.5 hours to obtain nitrogen-doped graphene nanosheets.
[0027] Furthermore, the usage ratio of graphene oxide nanosheets, deionized water and melamine is 5-10g:5-10L:25-50g.
[0028] Beneficial effects of the present invention:
[0029] (1) The surface of the microcrystalline glass baking tray prepared by the present invention contains a non-stick coating, which has good hydrophobic and oleophobic properties. The non-stick coating is bonded to the microcrystalline glass body through the porous structure of the microcrystalline glass, which has high bonding strength, large contact area, large heat conduction area, strong thermal conductivity, and the non-stick coating is not easy to crack, has a long service life, and is easy to clean.
[0030] (2) The microcrystalline glass baking tray made by the present invention is prepared by preparing a porous glass powder containing a foaming agent, and the porous glass powder is made into a coating under the adhesion effect of a polyvinyl alcohol aqueous solution, which is coated on the surface of a microcrystalline glass blank and heated to melt, so that the porous glass powder and the microcrystalline glass blank are fused, and a porous structure is formed on the surface of the microcrystalline glass blank under the action of the foaming agent. After polishing, a porous microcrystalline glass blank with a porous structure on the surface is obtained. The porous structure greatly enhances the bonding force between the non-stick coating formed by the suspension made of silicon dioxide and the porous microcrystalline glass blank, and the heat conduction area is larger.
[0031] (3) The production method of the present invention uses a foaming agent prepared by intercalating and compounding graphene nanosheets and mesoporous iron oxide nanosheets, and utilizes the gases generated by the combustion and oxidation of graphene nanosheets and mesoporous iron oxide at different temperatures to prepare a porous microcrystalline glass body. The graphene nanosheets burn in the presence of oxygen to produce carbon dioxide, which has better dispersion ability when passing through the iron oxide nanosheets with a mesoporous structure to form uniform and dense pores, thereby improving the stability of the porous microcrystalline glass body. The graphene nanosheets can also improve the thermal stability of the porous microcrystalline glass body, further improving the bonding strength and stability between the porous microcrystalline glass structure and the non-stick coating. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1: A method for producing a glass-ceramic baking tray, comprising the following steps:
[0034] S1. Put 40kg SiO2, 18kg Al2O3, 13kg MgO, 1.8kg K2O, 0.5kg CaO, 15kg Na2O, 5kg B2O3, 3kg TiO2, 2kg ZrO2 and 0.5kg Fe2O3 into a mixer and mix for 15 minutes, pour into a crucible and keep warm at 1350°C for 2 hours, then pour into water for quenching to obtain a glass block, dry the glass block at 110°C for 2 hours, crush and grind it into glass powder, re-melt the glass powder in a crucible at 1350°C and pour it into a graphite mold, transfer it to a muffle furnace at 500°C for annealing for 3 hours, and obtain a microcrystalline glass body after cooling.
[0035] S2. In a reactor, 5 g of graphene oxide nanosheets with a sheet diameter of 5 μm and a thickness of 3 nm were dispersed in 5 L of deionized water and ultrasonically dispersed for 1 h. 25 g of melamine was added to the reactor, and the temperature was raised to 80° C. and stirred for reaction for 12 h. The precipitate was collected by filtration and vacuum dried at 60° C. The dried powder was heated to 850° C. in an argon atmosphere and pyrolyzed for 1 h to obtain nitrogen-doped graphene nanosheets.
[0036] S3. Mix 20 mL of ammonia water, 60 mL of deionized water and 200 mL of ethanol in a reactor, dissolve tetraethyl orthosilicate in an equal volume of ethanol to obtain a mixed solution, slowly drop 40 mL of the mixed solution into the reactor, stir at 200 rpm for 3 h, dissolve 2 mL of phenyltriethoxysilane in 20 mL of ethanol, slowly drop the solution into the reactor, stir and react for 2 h, centrifuge and separate the solid, wash the precipitate with deionized water and ethanol, and dry at 50°C for 12 h to obtain modified silica nanospheres.
[0037] S4. Disperse 5 g of modified silica nanospheres in 0.5 L of ethanol in a reactor, heat to 60°C, add 5 g of nitrogen-doped graphene nanosheets, stir at 200 rpm for 3 h, filter and dry the precipitate at 70°C for 12 h to obtain silica / graphene nanosheets.
[0038] S5. Disperse 5 g of silica / graphene nanosheets in 0.8 L of propanol in a reactor, add 4 g of ferric nitrate nonahydrate into the reactor and stir to dissolve, then add 200 mL of glycerol, heat to 180 °C and react for 16 h. After cooling, wash with anhydrous ethanol and dry in vacuo at 60 °C. Calcine the dried powder at 350 °C in air for 2 h to obtain a foaming agent.
[0039] S6. Mix 50g of granite powder, 2.5g of foaming agent and 2g of calcium hydroxide to obtain a mixed powder, granulate the mixed powder with a 5wt% polyvinyl alcohol aqueous solution, press into a mold under a pressure of 70Mpa after granulation, dry at 100°C for 2h, then heat treat at 500°C for 2h to obtain a porous glass blank, crush and grind the porous glass blank and pass it through a 100-mesh sieve to obtain a porous glass powder.
[0040] S7. Disperse 50g of porous glass powder in 1L of 5wt% polyvinyl alcohol solution to obtain a coating material, and evenly coat the coating material on the microcrystalline glass body with a coating thickness of 0.1mm. Then place it in a mold and heat it at 500℃ for 2h. Transfer it to a muffle furnace and heat it to 1150℃ for 20min. After cooling, polish the surface with silicon carbide paper to make a porous structure appear on the surface to obtain a porous microcrystalline glass body.
[0041] S8. In a reaction kettle, add 3 mL of methyltrimethoxysilane to 150 mL of anhydrous ethanol, add 1 g of nano-silica with a particle size of 10 nm, magnetically stir for 5 hours, rotary evaporate to remove the solvent, dry at 90°C, add to a mixture of 100 mL of polydimethylsiloxane and 5 mL of n-hexane, and ultrasonically disperse to obtain a suspension. Spray the suspension evenly on the surface of the porous microcrystalline glass body with a spray gun, and then place it in an oven at 250°C to dry for 40 minutes. Repeat the spraying and drying until the surface of the porous microcrystalline glass body is smooth to obtain a microcrystalline glass baking tray.
[0042] Embodiment 2: A method for producing a glass-ceramic baking tray, comprising the following steps:
[0043] S1. Put 50kg SiO2, 19kg Al2O3, 15kg MgO, 2kg K2O, 0.55kg CaO, 16kg Na2O, 5.25kg B2O3, 4kg TiO2, 2.25kg ZrO2 and 0.55kg Fe2O3 into a mixer and mix for 17 minutes, pour into a crucible and keep warm at 1400°C for 2.5 hours, then pour into water and quench to obtain a glass block, dry the glass block at 115°C for 2.5 hours, crush and grind it into glass powder, re-melt the glass powder in a crucible at 1400°C and pour it into a graphite mold, transfer it to a muffle furnace at 525°C for annealing for 3.25 hours, and obtain a microcrystalline glass body after cooling.
[0044] S2. In a reactor, 7.5 g of graphene oxide nanosheets with a sheet diameter of 10 μm and a thickness of 5 nm were dispersed in 7.5 L of deionized water and ultrasonically dispersed for 1.25 h. 35 g of melamine was added to the reactor, and the temperature was raised to 85° C. and stirred for reaction for 14 h. The precipitate was collected by filtration and vacuum dried at 65° C. The dried powder was heated to 875° C. in an argon atmosphere and pyrolyzed for 1.25 h to obtain nitrogen-doped graphene nanosheets.
[0045] S3. Mix 25 mL of ammonia water, 70 mL of deionized water and 225 mL of ethanol in a reactor, dissolve tetraethyl orthosilicate in an equal volume of ethanol to obtain a mixed solution, slowly drop 50 mL of the mixed solution into the reactor, stir at 250 rpm for 3.5 h, dissolve 3 mL of phenyltriethoxysilane in 25 mL of ethanol, slowly drop the solution into the reactor, stir and react for 2.5 h, separate the solid by centrifugation, wash the precipitate with deionized water and ethanol, and dry at 55 °C for 13 h to obtain modified silica nanospheres.
[0046] S4. Disperse 7.5 g of modified silica nanospheres in 0.75 L of ethanol in a reactor, heat to 65° C., add 7.5 g of nitrogen-doped graphene nanosheets, stir at 250 rpm for 3.5 h, filter and dry the precipitate at 75° C. for 13 h to obtain silica / graphene nanosheets.
[0047] S5. Disperse 7.5 g of silica / graphene nanosheets in 0.9 L of propanol in a reactor, add 5 g of ferric nitrate nonahydrate into the reactor and stir to dissolve, then add 225 mL of glycerol, heat to 190 °C and react for 17 h. After cooling, wash with anhydrous ethanol and dry under vacuum at 65 °C. Calcine the dried powder at 360 °C in air for 2.25 h to obtain a foaming agent.
[0048] S6. Mix 75g of granite powder, 4g of foaming agent and 2.25g of calcium hydroxide to obtain a mixed powder, granulate the mixed powder with a 5wt% polyvinyl alcohol aqueous solution, press into a mold under a pressure of 75Mpa after granulation, dry at 105°C for 2.25h, then heat treat at 525°C for 2.25h to obtain a porous glass blank, crush and grind the porous glass blank and sieve it to obtain a porous glass powder.
[0049] S7. Disperse 75 g of porous glass powder in 1.25 L of 5 wt% polyvinyl alcohol solution to obtain a coating material. Evenly coat the coating material on the microcrystalline glass body with a coating thickness of 0.3 mm. Then place it in a mold and heat it at 525°C for 2.25 h. Transfer it to a muffle furnace and heat it to 1200°C for 22.5 min. After cooling, polish the surface with silicon carbide paper to make a porous structure appear on the surface to obtain a porous microcrystalline glass body.
[0050] S8. In a reactor, add 2.5 mL of methyltrimethoxysilane to 125 mL of anhydrous ethanol, add 0.75 g of nano-silica with a particle size of 15 nm, magnetically stir for 4.5 h, rotary evaporation to remove the solvent, dry at 85 °C, add to a mixture of 90 mL of polydimethylsiloxane and 4.5 mL of n-hexane, and ultrasonically disperse to obtain a suspension. Spray the suspension evenly on the surface of the porous microcrystalline glass body with a spray gun, and then place it in an oven at 225 °C to dry for 35 min. Repeat the spraying and drying until the surface of the porous microcrystalline glass body is smooth to obtain a microcrystalline glass baking tray.
[0051] Embodiment 3: A method for producing a glass-ceramic baking tray, comprising the following steps:
[0052] S1. Put 55kg SiO2, 20kg Al2O3, 18kg MgO, 2.2kg K2O, 0.6kg CaO, 17kg Na2O, 5.5kg B2O3, 5.5kg TiO2, 2.5kg ZrO2 and 0.6kg Fe2O3 into a mixer and mix for 20 minutes, pour into a crucible and keep warm at 1550℃ for 3 hours, then pour into water for quenching to obtain a glass block, dry the glass block at 120℃ for 3 hours, crush and grind it into glass powder, re-melt the glass powder in a crucible at 1550℃ and pour into a graphite mold, transfer to a muffle furnace at 550℃ for annealing for 3.5 hours, and obtain a microcrystalline glass body after cooling.
[0053] S2. In a reactor, disperse 10 g of graphene oxide nanosheets with a sheet diameter of 10 μm and a thickness of 10 nm in 10 L of deionized water and ultrasonically disperse them for 1.5 h. Add 50 g of melamine into the reactor and heat it to 90° C. and stir to react for 16 h. Collect the precipitate by suction and dry it in a vacuum at 70° C. Heat the dried powder to 900° C. in an argon atmosphere and pyrolyze it for 1.5 h to obtain nitrogen-doped graphene nanosheets.
[0054] S3. Mix 30 mL of ammonia water, 80 mL of deionized water and 250 mL of ethanol in a reactor, dissolve tetraethyl orthosilicate in an equal volume of ethanol to obtain a mixed solution, slowly drop 60 mL of the mixed solution into the reactor, stir at 300 rpm for 4 h, dissolve 4 mL of phenyltriethoxysilane in 30 mL of ethanol, slowly drop the solution into the reactor, stir and react for 3 h, separate the solid by centrifugation, wash the precipitate with deionized water and ethanol, and dry at 60 ° C for 14 h to obtain modified silica nanospheres.
[0055] S4. Disperse 10 g of modified silica nanospheres in 1 L of ethanol in a reactor, heat to 70°C, add 10 g of nitrogen-doped graphene nanosheets, stir at 300 rpm for 4 h, filter and dry the precipitate at 80°C for 14 h to obtain silica / graphene nanosheets.
[0056] S5. Disperse 10 g of silica / graphene nanosheets in 1 L of propanol in a reactor, add 6 g of ferric nitrate nonahydrate into the reactor and stir to dissolve, then add 250 mL of glycerol, heat to 200 °C and react for 18 h. After cooling, wash with anhydrous ethanol and dry in vacuo at 70 °C. Calcine the dried powder at 370 °C in air for 2.5 h to obtain a foaming agent.
[0057] S6. Mix 100g of granite powder, 5g of foaming agent and 2.5g of calcium hydroxide to obtain a mixed powder, granulate the mixed powder with a 5wt% polyvinyl alcohol aqueous solution, press into a mold under a pressure of 80Mpa after granulation, dry at 110℃ for 2.5h, then heat treat at 550℃ for 2.5h to obtain a porous glass blank, crush and grind the porous glass blank and pass it through a 100-mesh sieve to obtain a porous glass powder.
[0058] S7. Disperse 100 g of porous glass powder in 1.5 L of 5 wt% polyvinyl alcohol solution to obtain a coating material. Evenly coat the coating material on the microcrystalline glass body with a coating thickness of 0.5 mm. Then place it in a mold and heat it at 550°C for 2.5 hours. Transfer it to a muffle furnace and heat it to 1250°C for 25 minutes. After cooling, polish the surface with silicon carbide paper to make a porous structure appear on the surface to obtain a porous microcrystalline glass body.
[0059] S8. In a reaction kettle, add 3 mL of methyltrimethoxysilane to 150 mL of anhydrous ethanol, add 1 g of nano-silica with a particle size of 20 nm, magnetically stir for 5 hours, rotary evaporate to remove the solvent, dry at 90°C, add to a mixture of 100 mL of polydimethylsiloxane and 5 mL of n-hexane, and disperse by ultrasonication to obtain a suspension. Spray the suspension evenly on the surface of the porous microcrystalline glass body with a spray gun, and then place it in an oven at 250°C to dry for 40 minutes. Repeat the spraying and drying until the surface of the porous microcrystalline glass body is smooth to obtain a microcrystalline glass baking tray.
[0060] Principle of the invention:
[0061] A porous glass powder containing a foaming agent is prepared, the porous glass powder is made into a coating under the adhesion action of a polyvinyl alcohol aqueous solution, the coating is applied to the surface of a microcrystalline glass body and heated to melt, so that the porous glass powder and the microcrystalline glass body are fused, and a porous structure is formed on the surface of the microcrystalline glass body under the action of the foaming agent. After polishing, a porous microcrystalline glass body with a porous structure on the surface is obtained. The porous structure greatly enhances the bonding force between the non-stick coating formed by a suspension made of silicon dioxide and the porous microcrystalline glass body, the heat conduction area is larger, the thermal conductivity is improved, and the non-stick coating makes the prepared microcrystalline glass baking tray have good non-stick properties.
[0062] The foaming agent prepared by the present invention is prepared by intercalation and compounding of graphene nanosheets and mesoporous iron oxide nanosheets. The porous microcrystalline glass blank is prepared by utilizing the gases generated by combustion and oxidation of the graphene nanosheets and mesoporous iron oxide at different temperatures. The graphene nanosheets are burned in the presence of oxygen to generate carbon dioxide. The carbon dioxide has better dispersion ability after passing through the iron oxide nanosheets with a mesoporous structure, forming uniform and dense pores, thereby improving the stability of the porous microcrystalline glass blank. The graphene nanosheets can also improve the thermal stability of the porous microcrystalline glass blank, further improving the bonding strength and stability between the porous microcrystalline glass structure and the non-stick coating.
[0063] The graphene nanosheets used in the invention are graphene oxide nanosheets, which have good dispersibility in deionized water. Nitrogen-doped graphene oxide nanosheets are obtained by grafting with melamine in deionized water at high temperature. Modified silica nanospheres are obtained by modifying nano silica with phenyltriethoxysilane when preparing nano silica. The modified silica nanospheres are non-covalently assembled on nitrogen-doped graphene oxide nanosheets by utilizing the phenyl groups on the modified silica nanospheres. The modified silica nanospheres have the ability to disperse in alcohol solvents, so that the dispersibility of silica / graphene nanosheets in ethanol is improved. Then, iron oxide nanosheets with a mesoporous structure are in-situ generated between the silica / graphene nanosheet layers, and the foaming agent is obtained by assembly. The silica nanoparticles not only have good fusion with the microcrystalline glass blank when preparing the porous microcrystalline glass blank, but also have the effect of reducing the agglomeration of the nitrogen-doped graphene nanosheets. The foaming agent has good dispersibility in the obtained porous microcrystalline glass blank, and has the effect of improving the thermal conductivity of the microcrystalline glass baking tray.
[0064] Comparative Example 1: The difference from Example 1 is that in S4, the silicon dioxide / graphene nanosheets are replaced by nitrogen-doped graphene nanosheets of equal mass to prepare a microcrystalline glass baking tray.
[0065] Comparative Example 2: The difference from Example 1 is that in S6, the foaming agent is replaced by an equal mass of silicon dioxide / graphene nanosheets to prepare a microcrystalline glass baking tray.
[0066] Comparative Example 3: The difference from Example 1 is that in S7, a porous glass-ceramic body is replaced by a glass-ceramic body to produce a glass-ceramic baking tray.
[0067] The sources of some reagents in the examples and comparative examples of the present invention are as follows:
[0068] Graphene oxide nanosheets and nano-silicon dioxide were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0069] The performance of the glass-ceramic baking trays prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested. A contact angle meter (Dropmeter A-100) was used to measure WCA. The measurements were made 5 times at different locations on the surface of each sample and the average value was taken. The test water droplet was 7 μL. The glass-ceramic baking tray was then placed in a muffle furnace with a set temperature of 300°C. The heat treatment was performed for 4 hours. After cooling, the heat treatment was repeated 100 times, the WCA was measured again, and the WCA reduction rate was calculated. The thermal conductivity of the glass-ceramic baking tray was measured using a thermal conductivity meter (TPS2500S).
[0070] The results are shown in Table 1:
[0071]
[0072] It can be seen from Table 1 that the microcrystalline glass baking tray prepared by the present invention has a large water contact angle, indicating that it has super hydrophobic properties and good non-stick properties. After 100 heat treatments, the water contact angle decreases by about 2%. Multiple heat treatments have almost no effect on the non-stick properties of the microcrystalline glass baking tray, indicating that the microcrystalline glass baking tray of the present invention has high thermal stability, and the coating is not easy to crack and fail. At the same time, it has high thermal conductivity and can be heated to the preset temperature of the oven in a shorter time, resulting in better baking effect.
[0073] In Comparative Example 1, since modified silicon dioxide is not used to covalently bond with nitrogen-doped graphene nanosheets, the nitrogen-doped graphene nanosheets have poor dispersibility in ethanol, are easily agglomerated, and have poor foaming effect, and the resulting porous structure has low bonding strength with the non-stick coating.
[0074] Since the mesoporous iron oxide nanosheets were not in-situ synthesized in the silicon dioxide / graphene nanosheets in Comparative Example 2, the foaming effect was slightly lower than that of Examples 1 to 3.
[0075] Since no porous structure was added to Comparative Example 3, although the thermal conductivity was high, the water contact angle decreased significantly after multiple heat treatments, indicating that the bonding force with the non-stick coating was poor and the coating was easy to fall off.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for producing a glass-ceramic baking tray, characterized in that: The steps include: Step 1: Mix granite powder, a foaming agent and calcium hydroxide to obtain a mixed powder, granulate the mixed powder with a 5wt% polyvinyl alcohol aqueous solution, press it into a mold, dry it, heat it to 500-550°C for 2-2.5h, and obtain a porous glass body. Grind the porous glass body and pass it through a 100-mesh sieve to obtain a porous glass powder; Step 2: disperse the porous glass powder in a 5wt% polyvinyl alcohol solution to obtain a coating material, and evenly coat the coating material on the microcrystalline glass body with a coating thickness of 0.1-0.5mm, then place it in a mold and heat it to 500-550℃ for heat treatment for 2-2.5h, transfer it to a muffle furnace and heat it to 1150-1250℃ for reaction for 20-25min, and grind the surface after cooling to obtain a porous microcrystalline glass body; Step 3: Add methyltrimethoxysilane to ethanol in a reaction kettle, add nano-silica with a particle size of 10-20 nm, stir magnetically for 4-5 hours, remove the solvent by rotary evaporation, dry at 80-90°C, add polydimethylsiloxane and n-hexane, and disperse by ultrasonication to obtain a suspension, spray the suspension evenly on the surface of the porous microcrystalline glass body with a spray gun, and then place it in an oven at 200-250°C for drying for 30-40 minutes, repeat spraying and drying until the surface of the porous microcrystalline glass body is smooth and smooth, and obtain a microcrystalline glass baking tray; The foaming agent is prepared by the following steps: Disperse silicon dioxide / graphene nanosheets in propanol in a reaction kettle, add ferric nitrate nonahydrate into the reaction kettle and stir to dissolve, then add glycerol, heat to 180-200° C. and react for 16-18 hours, wash and dry after cooling, and calcine in air at 350-370° C. for 2-2.5 hours to obtain a foaming agent.
2. The method for producing a glass-ceramic baking tray according to claim 1, characterized in that: The usage ratio of the granite powder, the foaming agent and the calcium hydroxide in step 1 is 50-100 g: 2.5-5 g: 2-2.5 g; The usage ratio of the porous glass powder and the polyvinyl alcohol solution in step 2 is 50-100 g: 1-1.5 L; The dosage ratio of methyltrimethoxysilane, ethanol, nano-silica, polydimethylsiloxane and n-hexane in step 3 is 2-3mL: 100-150mL: 0.5-1g: 80-100mL: 4-5mL.
3. The method for producing a glass-ceramic baking tray according to claim 1, characterized in that: The usage ratio of the silicon dioxide / graphene nanosheets, propanol, ferric nitrate nonahydrate and glycerol is 5-10 g: 0.8-1 L: 4-6 g: 200-250 mL.
4. The method for producing a glass-ceramic baking tray according to claim 3, characterized in that: The silicon dioxide / graphene nanosheets are prepared by the following steps: Dispersing the modified silica nanospheres in ethanol in a reaction kettle, heating to 60-70° C., adding nitrogen-doped graphene nanosheets, stirring and reacting for 3-4 hours, and filtering and drying the precipitate to obtain silica / graphene nanosheets; The usage ratio of the modified silicon dioxide nanospheres, ethanol and nitrogen-doped graphene nanosheets is 5-10 g: 0.5-1 L: 5-10 g.
5. The method for producing a glass-ceramic baking tray according to claim 4, characterized in that: The modified silica nanospheres are prepared by the following steps: Ammonia water, deionized water and ethanol were mixed in a reaction kettle, ethyl orthosilicate was dissolved in an equal volume of ethanol to obtain a mixed solution, the mixed solution was slowly added dropwise to the reaction kettle and stirred for 3-4 hours, phenyltriethoxysilane was dissolved in ten times the volume of ethanol, and the solution was slowly added dropwise to the reaction kettle, stirred for reaction for 2-3 hours, the precipitate was washed by centrifugation, and the modified silica nanospheres were obtained after drying.
6. The method for producing a glass-ceramic baking tray according to claim 5, characterized in that: The dosage ratio of the ammonia water, deionized water, ethanol, mixed solution and phenyltriethoxysilane is 20-30mL: 60-80mL: 200-250mL: 40-60mL: 2-4mL.
7. The method for producing a glass-ceramic baking tray according to claim 4, characterized in that: The nitrogen-doped graphene nanosheets are prepared by the following steps: In a reaction kettle, graphene oxide nanosheets with a sheet diameter of 5-10 μm and a thickness of 3-10 nm are dispersed in deionized water and ultrasonically dispersed for 1-1.5 hours. Melamine is added to the reaction kettle, and the temperature is raised to 80-90° C. and stirred for reaction for 12-16 hours. The precipitate is collected by suction filtration and vacuum dried at 60-70° C. The dried powder is heated to 850-900° C. in an argon atmosphere and pyrolyzed for 1-1.5 hours to obtain nitrogen-doped graphene nanosheets.
8. The method for producing a glass-ceramic baking tray according to claim 7, characterized in that: The usage ratio of the graphene oxide nanosheets, deionized water and melamine is 5-10g:5-10L:25-50g.
9. A glass-ceramic baking tray, characterized in that: The microcrystalline glass baking tray is made by the production method of any one of claims 1 to 8.
Citation Information
Patent Citations
Production method of glass ceramic ovenware
CN107713776A
Nonstick glass baking tray and manufacturing method thereof
CN107973532A
Preparation method of graphene-mesoporous silica aerogel
CN104826582A
Graphene modified ceramic composite material, preparation method and product
CN112707736A